Update on oral health in elite sports - Raemy, A.; Merea Balestra, L.; Broome, M. (Swiss Sports & Exercise Medicine, 2020)
Since the first report from the 1968 Olympic Games, many studies have consistently reported poor oral health in elite athletes without any differences regarding socio-economic status or continental location. Poor oral health is an important issue as it has a clear impact on quality of life, confidence, appearance and socialisation. It also has an impact on sport performance and training with impaired preparation for competition. Many causes to impaired oral health can include nutritional diet and carbohydrate supplementation, oral dehydration, depression of various aspect of the immune function due to intense exercise, negative health behaviours, lack of awareness, time and prioritisation. Facial traumas and oro-dental injuries have to be considered because of their high prevalence among athletes. These findings were confirmed during the Lausanne 2020 Youth Olympic Games. This update tries to raise awareness of the issues of oral health amongst health-care providers and give simple interventions and strategies for prevention and promotion.